Pengaruh Latihan Plyometric Single Leg Bound dan Circuit Training terhadap Peningkatan Tendangan Sabit pada Siswa Pencak Silat - Risa Agus Teguh Wibowo; Iwan Arya Kusuma; Pipit Fitria Yulianto; Witri Suwanto; Dody Tri Iwandana; Jasmani Jasmani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the effect of single leg bound plyometric training and circuit training on increasing crescent kicks in pencak silat students. The research method used is an experimental method with a one group pretest-posttest design. The population in this study were 30 male students of the Pencak Silat Association of Setia Hati Terate (PSHT) Masaran Sragen, the sampling technique used was total sampling. The sample was divided into two groups, namely group 1 as many as 15 students received plyometric single leg bound exercise treatment and group 2 as many as 15 students received circuit training treatment. Data collection techniques were carried out by tests and measurements using the instructions for the pencak silat sickle kick speed test. The data analysis technique was carried out by statistical analysis using the t test at a significance level of 5%, to fulfill the assumptions of the results of the study a prerequisite analysis test was carried out, namely the normality test, homogeneity test, difference test and percentage increase. Based on the results of data analysis, this study resulted in the following conclusions: (1) There is a significant difference in effect between single leg bound plyometric training and circuit training. of ttable = 2.145 with a significance level of 5%. (2) circuit training has a better effect than plyometric single leg bound seen from the results of the percentage increase in the speed of the pencak silat sickle kick which shows that group 1 is 36.56% < group 2 is 62.06%. Keywords: Pencak Silat, Crescent Kick, Plyometric Single Leg Bound, Circuit Training